Effectiveness Of Corporate Social Responsibility (CSR) Program Of PT. Semen Baturaja (Persero) Tbk On Community Empowerment In Sukajadi Village, Baturaja Timur District, Ogan Komering Ulu Regency - Syaiful Amin; Munajat, Munajat; Rini Efrianti (International Journal of Economics, Business and Innovation Research, 2025)
Corporate Social Responsibility (CSR) is one of the activities carried out by a company as a form of responsibility, where the company has a responsibility towards the social and environmental community around it and the wider community in order to realize shared prosperity. This research will be conducted at PT. Semen Baturaja (Persero) Tbk in Sukajadi Village, Baturaja Timur District, OKU Regency. The determination of the location was carried out intentionally (Purposive) considering that PT. Semen Baturaja (Persero) Tbk is the main cement factory in South Sumatra. This study uses a qualitative descriptive approach. The sampling method used in this study is the stratified random sampling method. With a sample of 60 consisting of 30 people who received the CSR program and Employees. Analysis of the data processed in the study is primary and secondary data. The results of the study show the Realization of the Corporate Social Responsibility (CSR) program of PT. Semen Baturaja (Persero), Tbk. observations can be concluded that it has been running effectively. Analysis of the effectiveness of the Corporate Social Responsibility (CSR) Program of PT. Semen Baturaja (Persero), Tbk towards community empowerment is measured based on 6 indicators, namely increasing individual capacity, increasing economic welfare, health and welfare, social and political participation, infrastructure development and equality and inclusion